2021
DOI: 10.2991/assehr.k.210326.010
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study: Profile of Critical and Creative Thinking in Undergraduate Students of Biology Education Study Program, Universitas Negeri Yogyakarta

Abstract: This research is a preliminary study conducted to describe the profile of critical and creative thinking of undergraduate students of biology education at Universitas Negeri Yogyakarta (YSU). This research was conducted on 59 students who have active status as undergraduate students of the biology education program at YSU. The instrument used was a habit of mind instrument of critical and creative thinking in the form of a Likert scale questionnaire. After obtaining the data, then the data were analyzed descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Saefi et al (2016) reported that most prospective biology teacher students at the State University of Malang, Indonesia, have moderate and low critical thinking. In line with this, Rasis and Paidi (2021) also reported that the critical thinking skills of biology students at Yogyakarta State University Indonesia were also in the moderate category, while Anwar's research results indicated that the critical thinking skills of firstsemester biology students at a number of Indonesian universities still show low indications (Anwar et al, 2020). This demonstrates the need for efforts to improve critical thinking skills in biology education students.…”
Section: Introductionmentioning
confidence: 72%
“…Saefi et al (2016) reported that most prospective biology teacher students at the State University of Malang, Indonesia, have moderate and low critical thinking. In line with this, Rasis and Paidi (2021) also reported that the critical thinking skills of biology students at Yogyakarta State University Indonesia were also in the moderate category, while Anwar's research results indicated that the critical thinking skills of firstsemester biology students at a number of Indonesian universities still show low indications (Anwar et al, 2020). This demonstrates the need for efforts to improve critical thinking skills in biology education students.…”
Section: Introductionmentioning
confidence: 72%